Pendampingan Pencatatan Perkawinan sebagai Administrasi Kependudukan terhadap Masyarakat OAP di Kampung Matara - Rudini Hasyim Rado; Aldisa Arifudin; Restu Monika Nia Betaubun; Muhammad Saiful Fahmi; Eki Tolanda (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The Indigenous Papuan People (OAP) in Matara village still have several couples who only marry based on customary law so that they do not have legal certainty in the aspect of marriage as evidenced by a marriage certificate. The purpose of this service is not only to provide assistance and legal counselling on the importance of marriage registration but also to realise the orderly administration of population in Matara village through marriage through church marriage and civil registration. The implementation method is carried out in various stages, including starting from data collection, counselling and procedures for implementing marriage. The results of the service are 6 (six) couples who have performed traditional marriages but have not been recorded in the civil registry because religious marriages have not been held and recorded under state law